Suicidal ideation among mental health patients at hospital discharge: prevalence and risk factors - Wanying Mao; Reham Shalaby; Ernest Owusu; Hossam Eldin Elgendy; Belinda Agyapong; Ejemai Eboreime; Peter H. Silverstone; Pierre Chue; Xin-Min Li; Wesley Vuong; Arto Ohinmaa; Valerie Taylor; et al. (BMC Psychiatry)
Abstract Background Evidence indicates that suicide risk is much higher for psychiatric patients in the weeks immediately following discharge from the hospital. It is, therefore, crucial to evaluate suicide risk accurately at discharge to provide supportive and lifesaving interventions as appropriate. Aim: In this study, the prevalence and risk factors for suicide ideations were examined among patients ready to be discharged from psychiatric units in Alberta province, Canada. Methods Researchers conducted face-to-face meetings with potential participants to determine if they were interested in participating. Eligible individuals in this epidemiological cross-sectional study used an online quantitative survey to assess suicide ideations using the appropriate question contained in the Patient Health Questionnaire (PHQ-9) scale. Information was also gathered regarding patient demographics, clinical information, and responses to the Generalized Anxiety Disorder (GAD-7), and World Health Organization Well-Being Index (WHO-5) questionnaires. Results We recruited 1,004 patients from an initial pool of 1,437 patients. We found that the prevalence of suicidal ideation among patients about to be discharged was 48.9%, i.e., nearly half of all patients had active suicidal thinking prior to discharge. We found that factors that were most significantly associated with this were age, ethnicity, employment status, primary mental health diagnoses, anxiety, and poor well-being at baseline. Conclusion Here, in a large cohort of psychiatric patients in Alberta, Canada, we found that nearly half of patients being discharged from an acute psychiatric unit reported suicidal ideation. Given the increased short-term risk to this group, there is an urgent need for additional research on the underlying reasons and reliable predictors of suicidal ideation in these patients. Additionally, appropriate interventions and supportive services must be provided both prior and after discharge to mitigate this substantial risk.